Destruction Law of Borehole Surrounding Rock of Granite under Thermo-Hydro-Mechanical Coupling - Jinwen Wu; Zijun Feng; Shuping Chen; Wenmei Han (Geofluids)
The destruction of the rock that surrounds boreholes under thermo-hydro-mechanical coupling is an important factor for borehole stability in hot dry rock (HDR) geothermal energy extraction. Failure experiments for granite under triaxial stress (σ1>σ2>σ3) were conducted as 500°C superheated steam was transported through the borehole. High-temperature steam leads to large thermal cracks in the surrounding rock, which are randomly distributed around the borehole and gradually expand outwards. The randomly distributed thermally induced microcracks increase the complexity of the initial fracture morphology around the borehole and contribute to the appearance of multiple branch fractures. Fracture development is negligibly affected by ground stresses during the initial stages. However, fractures are deflected towards the maximum horizontal principal stress under ground stresses during later periods. During fracture propagation, high-temperature steam more easily penetrates the rock because its viscosity is lower than water. Towards the end of the crack expansion, the steam loses heat and liquefies, which increases the elongation resistance, and results in the arrest and intermittent expansion of the cracks.